The development of the woven plant encyclopedia of the Simpakng Dayak Tribe Ketapang Regency - Agnesia Jeni Saputri; Ari Sunandar; Mahwar Qurbaniah (University of Muhammadiyah Malang, 2024)
The Dayak Simpakng community in Batu Daya village, Simpang Dua sub-district, has knowledge of making plaits by utilizing plants in the surrounding environment. The introduction of woven plants to students needs to be done to preserve the knowledge and woven plants of the Dayak Simpang tribe. This research aims to develop an encyclopedia of Dayak Simpang woven plants that is valid and feasible to use in learning. This research is a Research and Development (R&D) research with the Borg and Gall model. The instruments used are validation sheets, questionnaires, observation sheets, and interview sheets. The data were analyzed using a Likert scale questionnaire. This research involved three material expert validators, three media expert validators, and three language expert validators. The development trials were conducted in small-scale trials and large-scale trials. A total of 42 students were involved in the trial with a division of 12 students in the small-scale trial, and 30 students in the large-scale test. The results of validation by material experts obtained 92.18% (very valid), the results of validation by media experts obtained 96.66% (very valid), and the results of linguist validation obtained 93.51% (very valid). Based on the results of the small-scale trial, the score was 85.06%, and the results of the large-scale trial obtained a score of 85.50%. These results show that the encyclopedia of woven plants is very feasible to use in learning and get a positive response.